2016
DOI: 10.1042/cs20160084
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic hope for HDAC6 inhibitors in malignancy and chronic disease

Abstract: Recent years have witnessed an emergence of a new class of therapeutic agents, termed histone deacetylase 6 (HDAC6) inhibitors. HDAC6 is one isoform of a family of HDAC enzymes that catalyse the removal of functional acetyl groups from proteins. It stands out from its cousins in almost exclusively deacetylating cytoplasmic proteins, in exerting deacetylation-independent effects and in the success that has been achieved in developing relatively isoform-specific inhibitors of its enzymatic action that have reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 172 publications
1
68
0
3
Order By: Relevance
“…Several studies have demonstrated the influence of HDAC6 in neurodegenerative, cardiovascular and renal diseases, as well as in inflammation [175] and viral response [84]. The role of the HDAC6 protein in cancer is also now well better understood.…”
Section: Hdac6 In CMLmentioning
confidence: 99%
“…Several studies have demonstrated the influence of HDAC6 in neurodegenerative, cardiovascular and renal diseases, as well as in inflammation [175] and viral response [84]. The role of the HDAC6 protein in cancer is also now well better understood.…”
Section: Hdac6 In CMLmentioning
confidence: 99%
“…5 Acetylation of lysine residues in the N-termini of histones neutralizes their positive charge, which weakens the interaction between histones and negatively charged DNA, thereby allowing enhanced accessibility of transcription factors to the DNA. [7][8][9][10][11] For instance, suberoylanilide hydroxamic acid (SAHA, also known as vorinostat) is a nonselective HDAC inhibitor that is the first US Food and Drug Administrationapproved hydroxamic acid-based drug for use in patients with cutaneous T-cell lymphoma. [7][8][9][10][11] For instance, suberoylanilide hydroxamic acid (SAHA, also known as vorinostat) is a nonselective HDAC inhibitor that is the first US Food and Drug Administrationapproved hydroxamic acid-based drug for use in patients with cutaneous T-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…6 Abnormalities in such epigenetic regulatory system are important factors in the development of diseases including cancer and neurodegeneration; therefore, HDACs are considered promising therapeutic targets for these diseases. [7][8][9][10][11] For instance, suberoylanilide hydroxamic acid (SAHA, also known as vorinostat) is a nonselective HDAC inhibitor that is the first US Food and Drug Administrationapproved hydroxamic acid-based drug for use in patients with cutaneous T-cell lymphoma. 3 HDAC6, which belongs to the class IIb, is a unique member because of its characteristic localization and functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylases (HDACs) are enzymes that play an integral role in several cellular processes by extracting the acetyl group from histone or non-histone proteins (5). Based on their homology to yeast orthologous, mammalian HDACs are classified into 4 classes: I (HDACs1, 2, 3, and 8), II (HDACs 4, 5, 6, 7, 9, and 10), III (SIRT1-7), and IV (HDAC11) (6). Histone deacetylase 6 (HDAC6) is a cytoplasmic protein that regulates several cellular processes through deacetylasedependent and/or deacetylase-independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%